Implementasi Program “Anidzom ‘Alatarqiatil Akhlak” di Ponpes Modern Al- Ihsan Bandung - Daffa Nashrul Zakariyya (UNISBA Press, 2023)
Abstract. This study aims to determine the implementation of the Anidzom 'Alatarqiatil Akhlak program, including the planning of the Anidzom 'Alatarqiatil Akhlak program, the implementation of the Anidzom 'Alatarqiatil Akhlak program, the evaluation of the Anidzom 'Alatarqiatil Akhlak program. This research is based on the idea that the more students get used to living with morals, the more it becomes a habit to live with morals. Based on this, the Al-ihsan Islamic boarding school always provides regulations that prioritize morals, to make it a habit for students in their daily lives. Anidzom 'Alatarqiatil Akhlak is a program to develop the morals of students, which this program can be interpreted in language is the rules of mora development, the method of coaching is using the discipline method as a way to be able to foster and foster the morals of students. To prove this, the researcher used qualitative research, through observation and interviews coupled with the existing archives, the researcher sought further information about the Anidzom 'Alatarqiatil Akhlak program, the selection of informants itself was aimed at caring for students and OPPM administrators. Based on the results of observations and interviews, students in this Islamic boarding school are accustomed to a life full of rules, where these rules will become habituation when they live after graduating from the boarding school, because if they are forced to get used to it it will become a habit, from this are the rules that exist in this boarding school must always include the formation of good santri morals. Coupled with an organized regulation and making a student organization a more lesson in order to get to know a good organization. Abstrak. Penelitian ini bertujuan untuk mengetahui implementasi program Anidzom ‘Alatarqiatil Akhlak, meliputi tentang perencanaan program Anidzom ‘Alatarqiatil Akhlak, pelaksanaan program Anidzom ‘Alatarqiatil Akhlak, pengevalusian program Anidzom ‘Alatarqiatil Akhlak. Penelitian ini bertolak pada pemikiran bahwa semakin santri membiasakan hidup dengan akhlak, maka semakin menjadi kebiasaan hidup dengan akhlak. Berdasarkan hal tersebut pondok pesantren Al-ihsan ini senantiasa memberikan peraturan-peraturan yang mengedepankan akhlak, untuk menjadikan suatu kebiasaan santri dalam kehidupan sehari-harinya. Anidzom ‘Alatarqiatil Akhlak ini merupakan suatu program untuk mengembangkan akhlak anak didik, yang mana program ini dapat diartikan secara Bahasa adalah peraturan pembinaan akhlak, cara pembinaannya dengan menggunakan metode tatatertib sebagai suatu cara untuk dapat membina dan memupuk akhlak anak didik. Untuk membuktikan hal tersebut peneliti menggunakan penelitian kualitatif, melalui observasi dan wawancara ditambah dengan arsip-arsip yang ada peneliti mencari keterangan lebih lajut terhadap program Anidzom ‘Alatarqiatil Akhlak ini, pemilihan informan itu sendiri ditujukan kepada pengasuhan santri dan pengurus OPPM. Berdasarkan hasil observasi dan wawancara, santri di pondok ini terbiasa dengan hidup yang penuh peraturan, yang mana aturan ini akan menjadi pembiasaan dikala hidup setelah lulus dari pondok, karna keterpaksaan jika dibiasakan maka akan jadi kebiasaan, dari hal ini lah peraturan yang ada dalam pondok ini harus senantiasa meliputi pembentukan akhlak-aklak santri yang baik. Ditambah dengan suatu peraturan yang terorganisir dan menjadikan suatu organisasi santri menjadi pelajaran lebih agar dapat mengenal suatu organisasi yang baik.